Pengembangan panduan permainan tradisional bugis-makassar dalam meningkatkan keterampilan sosial siswa - Oktaviana Kasim, Sinta Nurul (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2017)
The problems which was described in this study can be divided into two parts (1) How to develop the guidance of Bugis-Makassar Traditional Games as acceptable counseling guidance media based on the usefulness, accuracy, and relevancy in increasing social skill of students. (2) How to implement the guidance of Bugis-Makassar traditional games as counseling guidance media. The purposes of this study are (1) to develop the guidance of Bugis-Makassar Traditional Games as acceptable counseling guidance media based on the usefulness, accuracy, and relevancy in increasing social skill of students. (2) to know the implementation of Bugis-Makassar traditional games guidance as counseling guidance media. This study used development model developed by Borg and Gall which examines the development of this Bugis-Makassar traditional games media. Participants of this study in this small trial consist of 12 students. Data collection technique was questionnaire and interview. The results showed that (1) Bugis-Makassar traditional games guidance can be accepted based on the usefulness, accuracy, and relevancy in increasing social skill of students. (2) the guidance of Bugis-Makassar traditional games as counseling guidance media can be implemented properly in SMPN 8 Makassar.